PKM SOSIALISASI PENANGANAN PERTAMA CEDERA OLAHRAGA MENGGUNAKAN METODE RICE PADA KLUB SEPAK BOLA MANISA UTAMA DAN WALET FC SIDRAP - Arfandi Akkase; Haeril Haeril; Nur Indah Atifah Anwar; Andi Atssam Mappanyukki; Nurul Fadilah Aswar (KORSAcs: Jurnal Pengabdian Kepada Masyarakat, 2022)
There are still many people around us who do not understand how to properly handle injuries, especially regarding the first treatment if an injury occurs during exercise. This paper aims to provide an understanding and description to the widercommunity about the appropriate steps, especially for the first treatment of sports injuries with RICE method. The RICE method is an injury management method, whichaims to prevent further injury and reduce pain. The purpose of this community service is to providescientific provision in the field of handling sports injuries with the RICE method. The problems faced by partners in the implementation of this Community Partnership Program are that partners do not know about the application or use of the RICE method when a player is injured and also lacks knowledge about which types of injuries can be directly handled using the RICE method. Partners who are Manisa Utama dan Walet FC athletes feel firsthand the benefits of the training taught The implementation of community service activities regarding the first handling of injuries using the RICE method which has been carried out has been going well and smoothly. Partners who are soccer athletes feel firsthand the benefits of the training taught. The results of the interviews conducted, the partners feel that it is very important for sports activists to know, because of the lack of knowledge about the first treatment of injuries using the RICE method which is very useful for minimizing the occurrence of serious injuries and recurrence of injuries if not handled properly.